2022
DOI: 10.1186/s13613-022-01087-5
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare trajectory of critically ill patients with necrotizing soft tissue infections: a multicenter retrospective cohort study using the clinical data warehouse of Greater Paris University Hospitals

Abstract: Background Necrotizing skin and soft tissue infections (NSTIs) are rare but serious and rapidly progressive infections characterized by necrosis of subcutaneous tissue, fascia and even muscle. The care pathway of patients with NSTIs is poorly understood. A better characterization of the care trajectory of these patients and a better identification of patients at risk of a complicated evolution, requiring prolonged hospitalization, multiple surgical re-interventions, or readmission to the intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Our study has some strengths, including its multicentre design, with participating centres having developed specific multidisciplinary care bundle for NSTI [ 23 ]. The comparison to a multicentre cohort of non-neutropenic NSTI patients allowed us to assess the clinical and microbiological characteristics of neutropenic patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study has some strengths, including its multicentre design, with participating centres having developed specific multidisciplinary care bundle for NSTI [ 23 ]. The comparison to a multicentre cohort of non-neutropenic NSTI patients allowed us to assess the clinical and microbiological characteristics of neutropenic patients [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, we acknowledge that the association of G-CSF with survival could suffer from a risk of immortal time bias, although the delay between ICU admission and this therapeutic intervention was very short and we considered G-CSF as a time-dependent variable, thus making this risk theoretical. In our study we compared neutropenic patients to a previously described cohort of non-neutropenic patients [ 10 ]. The data of the non-neutropenic patients were obtained from a retrospective search in the French national hospital database in 13 centres from the Assistance Publique—Hôpitaux de Paris (APHP) network, while neutropenic patients were from 6 AP-HP centres and 12 other French hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient transfer should be considered if early surgery cannot be performed locally [24,25]. Postoperative reassessment, ideally including a second-look surgery, is warranted for all patients, either to make the diagnosis in case of initially reassuring surgical findings but no subsequent clinical improvement, or to perform further tissue debridement (a median of 2–3 surgeries are required per patient) [1,26 ▪ ,27].…”
Section: Managementmentioning
confidence: 99%
“…Better describing the care trajectory of these patients and being able to identify patients at risk of a complicated course, requiring prolonged hospitalization, multiple surgical re-interventions, or ICU readmission, is an essential prerequisite to improve their care. A recent retrospective cohort [26 ▪ ] showed that NSTI patients admitted to the ICU are important consumers of hospital care. Indeed, they frequently required multiple surgeries, the median duration of ICU and total hospital stay were 8 and 37 days respectively, with 62% of re-hospitalization within 6 months, including 10% in the ICU.…”
Section: Healthcare Trajectory and Impact On Quality Of Lifementioning
confidence: 99%